(3efXeGJ GdCYeGd GdMhGaR h GdecGaBJ (B:s (3HMK Ydej aj GdLhGfH GdGLJeGYjI h GdfaSjI h GdbGfhfjI (B/s - (3OGhO, eYeQs ((3GdbGgQI(B: s (3OGQ GdcJGH GdMOjK(B, s, 2006)
(3jVe GdMhGaR eaGgje CfhGY hfXQjGJ, fXGe hWQb JMOjO GdCLhQ GdJTLjYjI, GdMGLI hGdJMajR hGdecGaCI aj GdefXeGJ, YdGbI GdMhGaR hGdecGaBJ HGdeLJeY GdUfGYj hGdJfXje, GdMhGaR hGdecGaBJ aj GdYed GdUfGYj HGdYGde, GdMhGaR hGdecGaBJ aj GdfXGe GdUfGYj HGdLRGFQs
(3HjHdjhZQGajG(B: (3U U(B.363-376 (3GdedGMb U(B.377s
Keywords: (3EOGQI GdCYeGds; (3GdCLhQs; (3MhGaR GdGfJGLs; (3MhGaR h ecGaBJs